International Trade Value Analysis: Study of Economic Graph Analysis of Export and Import Volume of Migas & Non-Migas - Fadiya, Feny; Br Sinaga, Era Widia; Matondang, Khairani Alawiyah (Jurnal Ilmu Manajemen Profitability, 2024)
This study was conducted to determine the scale of comparison of the value of exports and imports of Migas and non-Migas in Indonesia. The research time period is 10 years with a sample population of Indonesian export and import data. Data was obtained through the Central Bureau of Statistics (BPS) and processed through descriptive qualitative methods and using economic line graphs. This research results in 1) The volume of Migas exports is on a stable scale, while the volume of non-Migas exports is on a more fluctuating scale and has a larger volume. 2) The volume of Migas imports is on a stable scale, while the volume of non-Migas imports is on a more fluctuating line and has a larger volume. 3) The value of Migas exports is on a stable scale, while the value of non-Migas exports fluctuates and increases and has a larger value. 4) The value of Migas imports is on a stable line scale, while the value of non-Migas imports fluctuates more and has a greater import value than Migas. Researchers concluded a suggestion that focuses on the government as the authority of international trade policy to further maximize policies related to the maximum value of exports rather than imports in order to maximize state revenue.